Analisis Lembar Kerja Peserta Didik (LKPD) Praktikum Uji Urin Berbasis ANCORB - Ghaida Sekarlita Fadha Supriadi; Bambang Supriatno; Sri Anggraeni (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2021)
Student Worksheet (LKPD), is a useful guide in conducting a practicum. This study aims to analyze, test, and reconstruct Student Worksheets (LKPD) that do not meet the established standards. The research method used is using a qualitative descriptive method, which analyzes the Student Worksheet (LKPD) of the urine test practicum contained in the Biology package book for class XI SMA from several curricula. The analysis was carried out on 10 Student Worksheets (LKPD) for urine testing from the Competency-Based Curriculum (KBK) (2004), Education Unit Level Curriculum (KTSP) (2006), and the 2013 Curriculum from competency aspects, practical aspects, and knowledge construction aspects. The results showed that, there were discrepancies in the Student Worksheet (LKPD) of the urine test on competency aspects, practical aspects, and knowledge construction aspects. Practically, the urine test Student Worksheet (LKPD) analyzed can be carried out properly, but some Student Worksheets (LKPD) are not in accordance with the predetermined standards. In addition, the existing Student Worksheets (LKPD) from the Competency-Based Curriculum (KBK) (2004), Education Unit Level Curriculum (KTSP) (2006), to the 2013 Curriculum, there is no change in the working procedures from the Competency-Based Curriculum (KBK). (2004) to 2013 Curriculum. Therefore, it is necessary to reconstruct the urine test Student Worksheet (LKPD) as an alternative to practicum in order to construct knowledge and develop students' thinking skills, so that practicum activities become more meaningful.